Analysis of Factors Affecting Public Sector Audit Quality in Indonesia - Nst, Dito Aditia Darma; Dinar Rizki; Khairunisa; Mahza; Ika Agustina Siahaa (Science Tech Group, 2026)
Public sector auditing plays a crucial role in ensuring accountability and transparency in the management of state finances. However, the quality of audits across government institutions remains uneven and is influenced by auditor competence, independence, understanding of audit standards, and the effectiveness of internal supervision. This study aims to identify issues in public sector auditing and analyze the factors affecting audit quality. The method employed is a literature review of relevant studies and regulations. The findings indicate that auditor competence and independence are the most decisive factors in improving the quality of public sector audits.